2020
DOI: 10.1038/s41598-020-78754-9
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular and sternoclavicular joint dislocations indicate severe concomitant thoracic and upper extremity injuries in severely injured patients

Abstract: Preliminary studies show that clavicle fractures (CF) are known as an indicator in the severely injured for overall injury severity that are associated with relevant concomitant injuries in the thorax and upper extremity. In this regard, little data is available for the rarer injuries of the sternoclavicular and acromioclavicular joints (SCJ and ACJ, respectively). Our study will answer whether clavicular joint injuries (CJI), by analogy, have a similar relevance for the severely injured. We performed an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…This finding coincides with preliminary examinations that suggest and have proven a high proportion of clavicular in addition to further additional injuries in general in MCI [24,34,35]. In a current registry study, more than every 10th case of a clavicle joint injury (SCJ and ACJ) in severely injured patients had an additional CF, a finding that is quite similar to our data [36]. This collective showed that 0.1% of all patients altogether were affected by a CCI [36].…”
Section: Incidence and Subtypes Of Combined Injuriessupporting
confidence: 92%
See 1 more Smart Citation
“…This finding coincides with preliminary examinations that suggest and have proven a high proportion of clavicular in addition to further additional injuries in general in MCI [24,34,35]. In a current registry study, more than every 10th case of a clavicle joint injury (SCJ and ACJ) in severely injured patients had an additional CF, a finding that is quite similar to our data [36]. This collective showed that 0.1% of all patients altogether were affected by a CCI [36].…”
Section: Incidence and Subtypes Of Combined Injuriessupporting
confidence: 92%
“…In a current registry study, more than every 10th case of a clavicle joint injury (SCJ and ACJ) in severely injured patients had an additional CF, a finding that is quite similar to our data [36]. This collective showed that 0.1% of all patients altogether were affected by a CCI [36]. Therefore, especially in everyday clinical practice, it is essential to further exclude contra-polar injuries, especially in the case of an injury in the sternoclavicular region but also in the case of any clavicular injury [15,37].…”
Section: Incidence and Subtypes Of Combined Injuriessupporting
confidence: 91%
“…3 Patients with polytrauma have a high prevalence of shoulder injuries of up to 28%, with 3% consisting of ACJ injuries, that are associated with severe thoracic injuries. 1,2 Data are reported as mean ± SD unless otherwise indicated. Boldface P values indicate a statistically significant difference between groups (P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with polytrauma have a high prevalence of shoulder injuries of up to 28%, with 3% consisting of ACJ injuries, that are associated with severe thoracic injuries. 1,2 It is not uncommon that distracting pain or disability from injuries may lead to undetected shoulder or ACJ injuries. The Advanced Trauma Life Support guideline 7 suggests evaluating breathing using chest radiography but does not recommend the exact radiographic technique (either supine or upright).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation